High-Dose Nadroparin Following Endovascular Aneurysm Treatment Benefits Outcome After Aneurysmal Subarachnoid Hemorrhage. Issue 2 (27th July 2017) - Post, Rene; Zijlstra, IJsbrand A.J; Berg, Rene van den; Coert, Bert A; Verbaan, Dagmar; Vandertop, W Peter
Abstract: BACKGROUND: Delayed cerebral ischemia (DCI) is one of the major causes of delayed morbidity and mortality in patients with aneurysmal subarachnoid hemorrhage (aSAH). OBJECTIVE: To evaluate the effect of high-dose nadroparin treatment following endovascular aneurysm treatment on the occurrence of DCI and clinical outcome. METHODS: Medical records of 158 adult patients with an aSAH were retrospectively analyzed. Those patients treated endovascularly for their ruptured aneurysm were included in this study. They received either high-dose (twice daily 5700 AxaIE) or low-dose (once daily 2850 AxaIE) nadroparin treatment after occlusion of the aneurysm. Medical charts were reviewed and imaging was scored by 2 independent neuroradiologists. Data with respect to in-hospital complications, peri-procedural complications, discharge location, and mortality were collected. RESULTS: Ninety-three patients had received high-dose nadroparin, and 65 patients prophylactic low-dose nadroparin. There was no significant difference in clinical DCI occurrence between patients treated with high-dose (34%) and low-dose (31%) nadroparin. More patients were discharged to home in patients who received high-dose nadroparin (40%) compared to low-dose (17%; odds ratio [OR] 3.13, 95% confidence interval [95% CI]: 1.36-7.24). Furthermore, mortality was lower in the high-dose group (5%) compared to the low-dose group (23%; OR 0.19, 95% CI: 0.07-0.55), also after adjusting for neurological status on admission (OR 0.21, 95% CI: 0.07-0.63). CONCLUSION: Patients who were treated with high-dose nadroparin after endovascular treatment for aneurysmal SAH were more often discharged to home and showed lower mortality. High-dose nadroparin did not, however, show a decrease in the occurrence of clinical DCI after aSAH. A randomized controlled trial seems warranted.